2016
DOI: 10.1016/j.jcrs.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Metaanalysis of intraocular lens power calculation after laser refractive surgery in myopic eyes

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 25 publications
0
43
1
3
Order By: Relevance
“…Abulafia et al [34] found that the Barrett True K No History formula had significantly smaller variance in prediction error than the Shammas formula and performed similar to the Haigis-L and Modified-Masket formulas. A meta-analysis by Chen et al [35] concluded that the clinical history method was significantly inaccurate in predicting postoperative refraction than the Haigis-L formula. The current study also had similar findings that formulas using no prior data (i.e., Barrett True K No History and Haigis-L) and refractive change after LASIK (i.e., Barrett True K) are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Abulafia et al [34] found that the Barrett True K No History formula had significantly smaller variance in prediction error than the Shammas formula and performed similar to the Haigis-L and Modified-Masket formulas. A meta-analysis by Chen et al [35] concluded that the clinical history method was significantly inaccurate in predicting postoperative refraction than the Haigis-L formula. The current study also had similar findings that formulas using no prior data (i.e., Barrett True K No History and Haigis-L) and refractive change after LASIK (i.e., Barrett True K) are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Haigis [7] found that the ME of the Haigis-L formula was not significantly different from 0. Chen et al [10] found through meta-analysis that Shammas c.d. with the Shammas-PL formula outperformed the Haigis-L formula in eyes after laser refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most methods can be classified into two groups: methods that need data before the LASIK that patients underwent and methods that were based only on current measurements. Usually, the data before LASIK are not available or reliable, and literature has shown that no-history approaches are superior [710], which are widely used in clinical practice now. A series of methods that are used for calculating corrected corneal power (K c ) are accepted for their accessibility and convenience.…”
Section: Introductionmentioning
confidence: 99%
“…Para determinar el poder del lente intraocular a implantar, de manera que el ojo operado quede lo mas cerca posible de la emetropía, se requiere conocer al menos dos datos: la longitud axial del ojo y el poder de la córnea. Basándose en estos datos (y otros adicionales en algunos casos) las fórmulas intentan predecir la posición en que se ubicará el lente intraocular, y posteriormente calcular su poder dióptrico ideal en un segundo paso 7,8,17 .…”
Section: Cálculo Del Poder De Los Lentes Intraocularesunclassified